PEMENUHAN HAK EKSEKUSI KREDITUR SEPARATIS DALAM PENJAMINAN DARI PERSPEKTIF UNDANG-UNDANG KEPAILITAN - Izaac Lucas Dominggus Lawalata (AkMen JURNAL ILMIAH, 2017)
This research aimstofulfill therights ofthe executioncreditorif the debtoris declared bank rupts eparatists. According to Article56 paragraph(1) Bankruptcy Lawwhich statesthat therights ofexecution creditor sseparatists us pended for 90days. In this regard, there is a discrepancy between the agency bank ruptcy collateral material. Therefore, creditorsare creditor sseparatist super preferred, preferred ful fillment ofbothin theexecutionthe debtandbankruptcy, the strongestpositionunhinderedby anything, including bankruptcy, and apart from separate creditors. It can be seenassetin Section 1155 subsection (1) of the Civil Codelien, Section1178 subsection(2) of the Civil Code Mortgage, Article 27 paragraph(3) of the fiduciary law, Article 21about security mortgage rights. Under such provisions, the secure creditor can prove that directlyimplement the right executionof the collateral objects belonging tothe debtor bank rupt without having tofollow theperiod of suspensionfor 90days, because the object ofthe guarantee isnotincluded inthe bankruptcy estate..